2009
DOI: 10.1242/dev.027565
|View full text |Cite
|
Sign up to set email alerts
|

TNFα-dependent hepatic steatosis and liver degeneration caused by mutation of zebrafishs-adenosylhomocysteine hydrolase

Abstract: Hepatic steatosis and liver degeneration are prominent features of the zebrafish ducttrip (dtp) mutant phenotype. Positional cloning identified a causative mutation in the gene encoding S-adenosylhomocysteine hydrolase (Ahcy). Reduced Ahcy activity in dtp mutants led to elevated levels of S-adenosylhomocysteine (SAH) and, to a lesser degree, of its metabolic precursor Sadenosylmethionine (SAM). Elevated SAH in dtp larvae was associated with mitochondrial defects and increased expression of tnfa and pparg, an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 81 publications
(103 reference statements)
1
77
0
Order By: Relevance
“…At present, the evolutionary relationship between these TNF-␣ family members is not resolved (86). A recent study using the zebrafish ducttrip (dtp) mutant phenotype model showed the involvement of zebrafish TNF-␣, but not TNF-␤, in hepatic steatosis and liver degeneration (87). Our results show that both carp TNF-␣ isoforms examined in this study are biologically active.…”
Section: Discussionmentioning
confidence: 57%
“…At present, the evolutionary relationship between these TNF-␣ family members is not resolved (86). A recent study using the zebrafish ducttrip (dtp) mutant phenotype model showed the involvement of zebrafish TNF-␣, but not TNF-␤, in hepatic steatosis and liver degeneration (87). Our results show that both carp TNF-␣ isoforms examined in this study are biologically active.…”
Section: Discussionmentioning
confidence: 57%
“…To further corroborate that reduced methionine content negatively impacts liver development, we examined a previously characterized methionine metabolism disruption: Ahcy functions to break down S-adenosylhomocysteine into adenosine and homocysteine, and ahcy mutant zebrafish display hepatic steatosis and liver degeneration, followed by larval death (Matthews et al, 2009). Morpholino knockdown of ahcy reduces liver size, as reflected in fabp10a expression, at 72 hpf.…”
Section: Methionine Rescues Liver Development Defects In Cnr Mutantsmentioning
confidence: 99%
“…S7). Interestingly, treatment of zebrafish with 5-azacytidine, an inhibitor of methylation at hemimethylated cytidine residues, has been shown to globally reduce CpG methylation in larvae by half without increasing tnfa expression (36). Because tnfa levels do not change, there may be a threshold level of demethylation that must be crossed to allow for activation of tnfa.…”
Section: Resultsmentioning
confidence: 99%